ANALISIS PENGARUH KUALITAS TIDUR TERHADAP KELELAHAN KERJA PADA KARYAWAN - Putri Nathalia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2026)
Work fatigue is one of the occupational health problems that can reduce productivity and increase the risk of work accidents. Sleep quality is an important individual factor that influences workers' physical and mental conditions. Poor sleep quality may lead to decreased alertness, reduced concentration, and increased fatigue levels. This study used a Systematic Literature Review (SLR) approach with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method to identify and synthesize scientific evidence regarding the effect of sleep quality on work fatigue among employees. Literature searches were conducted through Google Scholar and Publish or Perish for publications between 2021–2026 using the keywords “sleep quality” and “work fatigue.” Of the 30 identified articles, all met the inclusion criteria and were analyzed. The synthesis results indicate a consistent and significant relationship between poor sleep quality and increased work fatigue. Sleep duration, sleep disturbances, sleep latency, and sleep efficiency were the most frequently reported indicators. The Pittsburgh Sleep Quality Index (PSQI) was the most widely used measurement instrument.